Exploring the impact of cultural intelligence on multicultural literacy in university students: a serial mediation model of cultural exposure and cross-cultural communication skills - Haikuo, Liu (Frontiers in Psychology, 2025)
IntroductionCultural intelligence plays a central role in shaping students' ability to navigate diverse cultural environments, yet the mechanisms through which it influences multicultural literacy remain underexplored. This study investigates a serial mediation model to examine how cultural intelligence indirectly enhances multicultural literacy through two psychological pathways: cultural exposure and cross-cultural communication skills.MethodsData were collected from 412 university students in China using stratified random sampling, with validated instruments measuring each construct. Structural equation modeling using SmartPLS confirmed the reliability and discriminant validity of all constructs.ResultsThe results show that cultural intelligence has significant positive effects on both cultural exposure and cross-cultural communication skills. In turn, cultural exposure not only directly enhances multicultural literacy but also facilitates the development of communication skills, which subsequently contributes to multicultural literacy through a sequential mediation pathway.DiscussionThese findings offer theoretical and practical insights into how institutions can foster students' intercultural competence by enhancing both their opportunities for exposure and their interpersonal communication abilities.